Discovery of Bucculatrix koreana sp. nov. and newly recorded Bucculatrix duanwuia (Lepidoptera: Bucculatricidae) in Korea - Oh, Jae-In; Lee, Ji-Young; Kim, Sang-Yoon; Jeong, June-Hyeok; Song, Young-Gwang; Byun, Bong-Kyu (Zootaxa, 2024)
In this study, we describe a new species, Bucculatrix koreana sp. nov., and report B. duanwuia Liu, 2020, for the first time in Korea. Adults and genitalia of both species are illustrated. Additionally, we provide and discuss DNA barcode sequences for Bucculatrix species known from Korea.